Of silent maids, skilled gardeners and careful madams: gendered dynamics and strategies of migrant domestic workers in Accra, Ghana - Awumbila, M.; Teye, J.K.; Yaro, J.A. (Springer, 2017)
Recent studies indicate that many migrants are engaged mainly in the informal sector in low-paid, short-term, and insecure occupations in cities. Using a qualitative research approach, this paper examines the gendered experiences, livelihood strategies and wellbeing of migrants engaged in domestic work in Accra, Ghana. Employing structure-agency theoretical perspectives, the paper also discusses how migrant domestic workers employ their own agency to counter exploitation. The findings show clear gendered patterns of employment in domestic work, with men having stronger agency to negotiate better conditions of work and remuneration. The paper argues that despite the heterogeneity and diversity of the work conditions and experiences of domestic workers in Accra, the importance of gender as a crucial factor mediating the experiences of both male and female domestic workers and their impacts on their wellbeing must be recognised in policies to address and regulate domestic work in Ghana.
Journal Article
Keywords: Migration; Domestic work; Livelihoods; Gender; Informal sector